The Practice of Ijarah Agreement in Gold Pawn: An Islamic Law Study at Jambi Sharia Pawnshop - Fathoni, Kamal; Salma, Salmawati; Faruq, A. Faruk; Arifin, Muhammad Arifin; Thoriq, M Thoriq (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Cooperation in the form of wage-hire transactions, known as ijarah contracts, is one of the important forms of muamalah in everyday life, including in gold pawn financing at Pegadaian Syariah. In the gold pawn scheme, Pegadaian Syariah implements two contracts simultaneously, namely the rahn contract for debt guarantee and the ijarah contract for charging storage fees, whose compliance with sharia principles is a major concern. This research aims to fill the knowledge gap related to the application of two contracts in one transaction in Islamic Pawnshops, especially in the context of the DSN-MUI fatwa and Islamic law. This research uses a descriptive qualitative method with a case study approach through observation, interviews, and documentation at Pegadaian Syariah Jambi Branch. The results showed that the application of the ijarah contract and rahn contract in the gold pawn product at Pegadaian Syariah is in accordance with sharia principles, as regulated in DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 concerning Rahn and DSN-MUI Fatwa No. 26/DSN-MUI/III/2002 concerning Gold Rahn. Pegadaian Syariah does not use an interest system, but applies ijarah fees based on the value of the goods and the storage period. The financing facility of 95% of the gold's appraised value provides a fair financial solution for the community. The implications of this research provide a practical and theoretical basis for the development of sharia-based pawn products that are more transparent and equitable. Â